Conservation of native fauna in highly invaded systems: managing mammalian predators in New Zealand. Issue 6 (1st June 2016) - Pech, Roger; Maitland, Matt
Abstract: Programs to conserve native fauna in invaded ecosystems often aim to reduce the impacts of alien predators. This approach can lead to unexpected outcomes in the native and the remaining invasive components of restored ecosystems. In New Zealand, suppression and eradication of invasive mammalian predators are well‐established conservation strategies, particularly on offshore islands and in mainland ecosanctuaries. Predator control has achieved important conservation gains over increasingly large areas but these can be offset by the ecological release of other uncontrolled pest species. In addition, novel ecosystems created by selective predator control and reintroductions of locally extinct or depleted native species may have unexpected trajectories as they evolve. Effective conservation requires new techniques for controlling entire suites of invasive predators over large areas, routine monitoring of the conservation outcomes of predator control, and better understanding of how modified, and in some cases reconstructed, seminatural ecosystems change when invasive predators are removed.